(3eHGgL GdacQ hefGgL GdYHQ aj EHQGR hOGFY GdaWQ ef GMQGR HOGFY GdUhQs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW,J (B718 (3g` s ((3CMeO Hf eMeO Gdbdbjdi s)
(3ChdgG (B:s
(3hHYO (B: (3aEfi de CRd ef bHd Cf jHdZ beQ YeQI GdEHOGQ eJNPG GdhQGbI UfGYI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B143s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B55 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B179 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs